Effects of ammoniumiron-hexacyanoferrate on the accumulation of radiocesium in reindeer - Hove, K.; Staaland, H.; Pedersen, Ø. (Rangifer, 1988)
It is concluded that a sustained release bolus for administration of a cesium binder of the ironhexa-cyanoferrate type provides a promising method for reduction of radiocesium uptake from contaminated pastures. Included is also a discussion after Hove’s lecture.